ANALYSIS OF MAXIM VIOLATION IN THE NOVEL ALL THE BRIGHT PLACES BY JENNIFER NIVEN - Sigarlaki, Triqzy Moniq; Mogea, Tini; Maukar, Merlin Maya (SoCul: International Journal of Research in Social Cultural Issues, 2024)
As a popular young adult novel, All the Bright Places frequently portrays characters who often violate Grice’s maxim violation when dealing with sensitive and emotional situations. Analyzing these maxim violations is important because it facilitates a more comprehensive understanding of the author’s intentional construction of dialogue to reveal pragmatic meanings, particularly maxim violations within the Cooperative Principle. This study aims to analyze violations of Grice’s Cooperative Principle in the novel All the Bright Places by Jennifer Niven, focusing on dialogues between Theodore Finch and Violet Markey. This study employs a descriptive qualitative method. The data are taken from dialogues between the two main characters in the novel All the Bright Places by Jennifer Niven and are collected through documentation and note-taking techniques. The data are analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing/verification, based on Grice’s Cooperative Principle and interpreted using Brown and Levinson’s politeness theory.The findings show that these maxim violations are used as communication strategies to avoid discussing sensitive topics, maintain personal boundaries, and manage social interaction dynamics. Brown and Levinson’s politeness theory is applied to explain the reasons behind these violations, such as efforts to protect face and avoid emotional conflicts. These findings contribute to the development of pragmatic theory and enrich literary studies, especially on how maxim violations deepen characterization and enhance narrative complexity. This study is expected to benefit students, educators, and researchers in linguistics, pragmatics, and literature.